1999
DOI: 10.1002/(sici)1521-4141(199905)29:05<1467::aid-immu1467>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

CD45 modulation of CXCR1 and CXCR2 in human polymorphonuclear leukocytes

Abstract: All leukocytes express the cell surface glycoprotein CD45, which has intrinsic intracellular protein tyrosine phosphatase activity. CD45 is known to play a regulatory role in activation-induced signaling in lymphocytes; however, little is known of its role in non-lymphoid leukocytes. Therefore, we examined the potential effect of CD45 on chemokine-induced signaling in human neutrophils (polymorphonuclear cells, PMN). Treating isolated PMN for 2 h with an anti-CD45RB antibody (Bra11) down-modulated expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
1
7
0
2
Order By: Relevance
“…Alternatively, the reduced expression of CXCR1 and CXCR2 could be explained by the presence of TNF‐ α , which leads to a proteolytic degradation of IL‐8 receptors [35]. Apart from soluble cell mediators, triggering of CD45 tyrosine phosphatase activity has been shown to down‐regulate IL‐8 receptors on neutrophils via tyrosine kinase activation in vitro [36]. Different sentivivity of chemokine receptors to regulatory intracellular signalling pathways or proteolytic clipping could contribute to the differential expression of receptors on activated leucocytes at the site of inflamation.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the reduced expression of CXCR1 and CXCR2 could be explained by the presence of TNF‐ α , which leads to a proteolytic degradation of IL‐8 receptors [35]. Apart from soluble cell mediators, triggering of CD45 tyrosine phosphatase activity has been shown to down‐regulate IL‐8 receptors on neutrophils via tyrosine kinase activation in vitro [36]. Different sentivivity of chemokine receptors to regulatory intracellular signalling pathways or proteolytic clipping could contribute to the differential expression of receptors on activated leucocytes at the site of inflamation.…”
Section: Discussionmentioning
confidence: 99%
“…31 Pretreatment of neutrophils with the anti-CD45 mAb Bra11 reduces cells surface expression of CXCR1 and CXCR2. 32 This effect is completely tyrphostin reversible. 32 We used Bra55, another anti-CD45 mAb that deactivates neutrophil chemotaxis without affecting receptor density, 32 and found that the inhibition of AT III-induced directed migration by Bra55 was reversed by tyrphostin.…”
Section: The Receptormentioning
confidence: 94%
“…32 This effect is completely tyrphostin reversible. 32 We used Bra55, another anti-CD45 mAb that deactivates neutrophil chemotaxis without affecting receptor density, 32 and found that the inhibition of AT III-induced directed migration by Bra55 was reversed by tyrphostin. Furthermore, the addition of tyrphostin abrogated AT III-induced deactivation of IL-8-triggered chemotaxis and thereby restored the migration of neutrophils to IL-8.…”
Section: The Receptormentioning
confidence: 94%
“…At the cellular level, the CD45 phosphatase targets several families of proteins, including the Src family tyrosine kinases and Janus kinases (41), resulting in positive or negative signaling (2, 4, 54). In addition to lymphocytes, recent studies demonstrate that CD45 can modulate activation and proliferation of several inflammatory cell types including granulocytes, mast cells and monocyte-lineage cells, broadening its role as a regulator of inflammatory responses (8, 20, 35, 48, 57). …”
Section: Introductionmentioning
confidence: 99%